Peran Aplikasi Dana Sebagai Mediator Antara Literasi Keuangan Digital Dan Perilaku Keuangan Impulsif Generasi Z - Febrisal Sahat; Hurriyaturrohman Hurriyaturrohman; Yudiana Yudiana (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The development of financial technology (fintech) has driven significant changes in society's transaction behavior, particularly among Generation Z, who constitute the largest user group of digital financial services. The convenience of transacting through digital wallet applications such as DANA offers various benefits in payment activities; however, it also has the potential to increase impulsive financial behavior if not balanced with sound financial management capabilities. This study aims to analyze the effect of digital financial literacy on impulsive financial behavior, with the use of the DANA application as a mediating variable, among students of the Management Study Program, Faculty of Economics and Business, Ibn Khaldun University Bogor. The research employs a quantitative approach using an explanatory research method. Data were collected through questionnaires distributed to 100 active student users of the DANA application, selected using a purposive sampling technique. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results show that digital financial literacy has a positive and significant effect on the use of the DANA application. However, digital financial literacy does not have a significant effect on impulsive financial behavior. Conversely, the use of the DANA application has a positive and significant effect on impulsive financial behavior. Furthermore, the DANA application is proven to mediate the relationship between digital financial literacy and impulsive financial behavior. These findings indicate that improving digital financial literacy needs to be accompanied by greater control over the use of digital financial services in order to reduce the tendency toward impulsive financial behavior among Generation Z.